Question
Asked Oct 24, 2019
fullscreen
check_circle

Expert Answer

Step 1

Given:

The function is y =c,e* +c^e^
help_outline

Image Transcriptionclose

The function is y =c,e* +c^e^

fullscreen
Step 2

Apply the initial condition as follows.

the initial condition y(0)= 4, y' (0) = 2.
y(0) e +ce)
4 G(1) (1)
...1)
4 c
y Ge-ce
y(0)-ce° - cze
2 = (1)-c2(1)
...2)
2 C-C2
Solve equation (1) and (2) we get, c 3 and c, =1
Thus, the initial condition y(0)= 4, y'(0)= 2 match with c, 3 and c2 =1
help_outline

Image Transcriptionclose

the initial condition y(0)= 4, y' (0) = 2. y(0) e +ce) 4 G(1) (1) ...1) 4 c y Ge-ce y(0)-ce° - cze 2 = (1)-c2(1) ...2) 2 C-C2 Solve equation (1) and (2) we get, c 3 and c, =1 Thus, the initial condition y(0)= 4, y'(0)= 2 match with c, 3 and c2 =1

fullscreen
Step 3

Apply the initial condi...

fullscreen

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Solutions are written by subject experts who are available 24/7. Questions are typically answered within 1 hour.*

See Solution
*Response times may vary by subject and question.
Tagged in

Math

Calculus

Derivative